Impact of export promotion programs on export performance - Jorge Mota; António Moreira; Alexandra Alves (Economies, 2021)
This research examines the relationship of Export Promotion Programs (EPPs), sponsored by a Portuguese Regional Association for Development on Trade and Industry, with firms' export performance. To investigate this, two models were applied using panel data analyses that relate export performance to variables such as participation in EPPs, age and size of firms. Data on 198 firms for the sampling period 2010 and 2018 was drawn from a Portuguese Regional Development Association and SABI (Iberian Balance sheet Analysis System) database. The results show that participation in EPPs does have a positive influence on the export performance of firms, especially for those firms with previous export experience, demonstrating the importance of using these programs. Findings also document that firm size relates positively export performance, whereas firms age show a negative effect on export performance, suggesting that larger firms with more resources positively influence exports and an increase in firms' age may increase their cultural inertia, inability to change strategies, decreasing their export performance, respectively. Finally, the participation in EPPs seems not to influence export performance for firms without previous export experience. The research contributes to the literature providing evidence on the role of EPP on firms' export performance behavior promoted by regional development associations.
Keywords: 330; internationalization; export intensity; export promotion programs